Pengaruh Non Performing Financing, Financing to Deposit Ratio dan Inflasi Terhadap Efisiensi Menggunakan Rasio Bopo Pada Bank Syariah di Indonesia Periode 2010-2015 - Shinta Puspitasari Hidayat; Ari Prasetyo (Universitas Airlangga, 2017)
This research attempt to analyze the effect of variableNon Performing Financing (NPF), Financing to Deposit Ratio (FDR) and inflation towards BOPO in syariah public bank and syariah business unit in Indonesia. This research uses qualitative approach. The data used in here is monthly data during 2010-2015. Typedof data used are the secondary data from official website Indonesian Bank. The analysis method used is multiple linear regression analysis method with significance level of 0,05. The result shows that non performing financing partially affects significantly towards BOPO ratio. Financing to deposit ratio and inflation don't affect significantly towards BOPO ratio. However, non performing financing, financing to deposit ratio and inflation simultaneously affect significantly towards the ratio of BOPO.